Evaluation practices of Post Graduate Diploma in Education Secondary School Student Teachers in Mhondoro Ngezi of Zimbabwe - Musankuleni Kaputa, Thomas (IJRDO - Journal of Social Science and Humanities Research, 2017)
This study assessed the importance of evaluation in the teaching and learning process. Evaluation is one way in which teaching and learning is measured for its worthiness and decisions made on how it should progress. Therefore evaluation is important in the classroom to establish if the teacher is on the right track and to ensure that the children are learning. The main research question of this study was ‘How important is evaluation in the teaching and learning process?’ The study used a qualitative approach to generate the data. The study was carried out in the Mhondoro - Ngezi district of Mashonaland West region. The population was all the Zimbabwe Open University (ZOU) Post graduate diploma secondary school students teachers who were in their final semester. A sample of 25 teachers were seen. The respondents were conveniently selected in the schools as the researcher focused on those students teachers who were allocated to him on a particular day. These student teachers taught various subjects ranging from languages to mathematics. Lesson observations, interviews and document analysis were used to generate the data. The findings showed that the teachers used both formative and summative evaluation in the teaching and learning process. Evaluations were mainly routine as they did not relate to the teaching and learning process most of the times. There was little evidence of evaluations on the rest of the records kept. The major recommendation is that student teachers on staff development should be capacitated in proper evaluation methods of the records they keep to improve the teaching and learning process in their classrooms.